Association Between Plasma Trans-Fatty Acid Concentrations and Measures of Glucose Homeostasis and Cardiovascular Risk Factors in Adults in NHANES 1999-2000. (August 2018) - Mazidi, Mohsen; Cicero, Arrigo F.; Kengne, Andre Pascal; Banach, Maciej
There is limited evidence on the association between plasma trans -fatty acids (TFAs) and cardiometabolic risk factors. Therefore, we examined the association between plasma TFA concentrations and glucose homeostasis and cardiovascular (CV) risk factors in adult Americans from the 1999 to 2000 National Health and Nutrition Examination Survey participants. Derivatized TFAs were separated by capillary gas chromatography. Of the 1678 participants, 46.5% were men. The mean age was 50.5 years overall, with no significant difference between men and women ( P = .101). In age-, sex- and race-adjusted analyses, mean waist circumference, fat-free mass, fat mass, C-peptide, insulin, hemoglobin A1c (HbA1c ), homeostatic model assessment of insulin resistance (HOMA-IR), serum triglycerides (TGs), and total cholesterol (TC) increased across increasing quarters of TFAs (for all P < .001), while mean serum high-density lipoprotein cholesterol decreased across increasing quarters of plasma TFAs ( P < .001). In multivariable adjusted linear regressions, there remained significant positive associations between all plasma TFAs and body mass index, waist circumference, fat-free mass, fat mass, C-peptide, insulin, fasting blood glucose, HOMA-IR, HbA1c, TGs, low-density lipoprotein cholesterol, and TC ( P < .001). In conclusion, our findings support a possible association between plasma TFAs concentrations and measures of glucose homeostasis and several CV risk factors.